Between‐family variation and quantitative genetics of developmental instability of long bones in rabbit foetuses. (25th March 2013) - Breno, Matteo; Bots, Jessica; Van Dongen, Stefan
<x xml:space="preserve">Abstract</x> The genetic basis of developmental instability (DI) remains largely unknown as a result of its morphological expression, fluctuating asymmetry (FA), poorly reflecting DI, especially if few traits are studied. The typically low values of heritability of FA (h2FA) can be translated into higher values of DI (h2DI) by the hypothetical repeatability, yet leading to wide confidence intervals. Thus, high sample sizes and/or several traits are indispensible for reaching meaningful conclusions. To obtain more insights into quantitative genetic variation of DI, we investigated between‐family variance in DI in six long bones of 1126 foetuses of the New Zealand white rabbit from a full‐sib experiment. We applied different approaches to obtain genetic parameters for DI. Heritabilities and the coefficients of between‐family variation (CVB) were calculated for six individual traits and composite indices. The results obtained, despite a likely upward bias as a result of maternal and non‐additive effects, lend support to the presence of moderate additive genetic variance for DI. It is suggested that, in foetal traits, the environmental variance was minimal, leading to a high likelihood of detecting genetic variation in DI, thus creating an ideal model system for studying the genetic basis of DI. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 33–42.